Dietary Allicin Improved the Survival and Growth of Large Yellow Croaker (Larimichthys crocea) Larvae via Promoting Intestinal Development, Alleviating Inflammation and Enhancing Appetite - Huang, Wenxing; Yao, Chuanwei; Liu, Yongtao; Xu, Ning; Yin, Zhaoyang; Xu, Wenxuan; Miao, Youqing; Mai, Kangsen; Ai, Qinghui (Frontiers in Physiology, 2020)
A 30-day feeding experiment was conducted to investigate effects of dietary allicin on survival, growth, antioxidant capacity, innate immunity and expression of inflammatory and appetite related genes in large yellow croaker larvae. Four iso-nitrogenous (53% crude protein) and iso-lipidic (19% crude lipid) diets were formulated via supplementing graded levels of allicin (0.0% (the control), 0.005%, 0.01% and 0.02% dry diet, respectively). Results showed that, among dietary treatments, larvae fed the diet with 0.005% allicin had the highest survival rate (SR) (P < 0.05), while larvae fed the diet with 0.01% allicin had the highest specific growth rate (SGR) (P < 0.05). Activities of amylase in both pancreatic segments (PS) and intestine segments (IS) of larvae fed the diet with 0.01% allicin were significantly lower than that in the control (P < 0.05). On the other hand, the supplementation of 0.01% allicin in diets significantly increased activities of alkaline phosphatase (AKP) and leucine aminopeptidase (LAP) in the intestinal brush border membrane (BBM) of larvae than the control (P < 0.05), indicating the promoting roles of allicin on fish larval intestinal development. Moreover, compared to the control, both the nitric oxide (NO) content and the activity of nitric oxide synthase (NOS) were significantly up-regulated in larvae fed the diet with 0.005% allicin, and catalase (CAT) were significantly upregulated in larvae fed the diet with 0.02% allicin (P < 0.05). Transcriptional levels of pro-inflammatory genes including cyclooxygenase-2 (cox-2), interleukin-1β (il-1β) and interleukin-6 (il-6) significantly decreased with increasing allicin, compared to the control. The expression of appetite genes including npy, ghrelin and leptin significantly increased with the prolonged fasting period, and dietary allicin supplementation significantly increased the transcriptional level of neuropeptide Y (npy) at 0.01%, while increased the transcriptional level of leptin in larvae at 0.02% dosages (P < 0.05). These results showed that the supplementation of 0.005% - 0.01% allicin in diets could improve the survival and growth of the large yellow croaker larvae probably by promoting intestinal development, alleviating inflammation and enhancing appetite.